PENGEMBANGAN DESAIN MOTIF BATIK SEBAGAI SARANA EDUKASI EKONOMI KREATIF SMA SWASTA NASIONAL - Siti Nurannisaa P.B.; Anastasia Cinthya Gani; Maitri Widya Mutiara (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Preservation of batik needs to be balanced with increasing the competitiveness of the industry. One of the strategies is to differentiate by creating new batik motifs in various variations and applications in various products as potential creative industries. Batik's design motif can be adjusted to the needs of the designer's interest. Activities that can be done are to build interest in batik in the current generation, especially school-age students through the development of batik motif designs. This community service program was conducted by the Faculty of Fine Arts and Design, Universitas Tarumanagara. The activity has the aim to develop batik design motifs for creative economic education and is attended by high school students. The training is conducted using an online meeting application and broadcast via social media sites. The method used is an experience-based training program or experiential learning. Participants combine knowledge, skills, and values through hands-on experience doing the practice of designing batik motif designs according to the theme of interest using creative thinking strategies with techniques of sketching directed and random images in their visual exploration. Various modifications and the creation of new batik design motifs produced by students indicate a sense of interest in batik culture. Strengthening the potential and power of education since school age becomes an insight to preserve and develop the creative industry. Systematic integration of education is required through the extracurricular and extracurricular teaching on batik motif design as one of the local content.